On-line/Off-line Identity-based Signature Scheme with Strong Unforgeability in the Standard Model. Issue 2 (August 2019) - Yang, Xiaodong; Chen, Chunlin; Ma, Tingchun; Li, Yutong; Xiao, Likun
Abstract: To solve the problems of low efficiency of the strong unforgeable identity-based signature scheme, a new strong unforgeable on-line/off-line identity-based signature scheme in standard model is proposed. Our new scheme uses the chameleon hash function and divides the signature algorithm into two stages: on-line stage and off-line stage. Our scheme generates signatures in a very short time, which efficiently improves the performance of the signature. The analysis results show that the proposed scheme not only has higher security, but also has lower computation cost.